Education for Environmental Sustainability: A Green School Development - Suryani, Adi; Soedarso, Soedarso; Saifulloh, Mohammad; Muhibbin, Zainul; Wahyuddin, Wahyuddin; Hanoraga, Tony; Nurif, Muhammad; Trisyanti, Umi; Rahadiantino, Lienggar; Rahmawati, Deti (Institut Teknologi Sepuluh Nopember, 2019)
Natural environment should be cared and sustained. It is a place for human to live and develop their social and economical world. Moreover, it is also a site for many biodiversity to live together in a balanced ecosystem. Recently, global awareness is directed to the alarming destruction of environment and its’ potential threats for human and other living things, as the impacts of human social-economical activities. Many efforts are executed to avoid or minimize future environmental damage. One of those endeavours is environmental education for young generation. Growing children’s environmental knowledge, protection skills and management as well as caring and responsible character can be an endurant solution. This study aims to examine some learning aspects in environmental education through green school development in MI Walisongo, Desa Sawohan, Sidoarjo. The study is based on a qualitative inquiry conducted by using direct participant observation as its’ data collection method. The study finds that environmental education requires a wide range of learning experiences, relating to emotion, direct practice and cognition development. In Green School MI Walisongo Desa Sawohan, those experiences are manifested into several learning processes: participative learning, modeling, character building, green site building, learning through game and peer team working.